Diphtheria in Lao PDR: Insufficient Coverage or Ineffective Vaccine? - Nanthavong, Naphavanh (PLoS One, 2015)
BACKGROUND: During late 2012 and early 2013 several outbreaks of diphthe-ria were notified in the North of the Lao People’s Democratic Republic. The aim of this study was to determine whether the re-emergence of this vaccine-preventable disease was due to insufficient vaccination coverage or reduction of vaccine effectiveness within the affected regions. METHODS: A serosurvey was conducted in the Huaphan Province on a cluster sampling of 132 children aged 12–59 months. Serum samples, socio-demographic data, nutri-tional status and vaccination history were collected when available. Anti-diphtheria and anti-tetanus IgG antibody levels were measured by ELISA. RESULTS: Overall, 63.6% of participants had detectable diphtheria antibodies and 71.2% tetanus antibodies. Factors independently associated with non-vaccination against diphtheria were the distance from the health centre (OR: 6.35 [95% CI: 1.4–28.8], p = 0.01), the Lao Theung ethnicity (OR: 12.2 [95% CI:1,74–85, 4], p = 0.01) and the lack of advice on vac-cination given at birth (OR: 9.8 [95% CI: 1.5–63.8], (p = 0.01) while the level of maternal edu-cation was a protective factor (OR: 0.08 [95% CI: 0.008–0.81], p = 0.03). Most respondents claimed financial difficulties as the main reason for non-vaccination. Out of 55 children whose vaccination certificates stated that they were given all 3 doses of diphtheria-containing vaccine, 83.6% had diphtheria antibodies and 92.7% had tetanus antibodies. Furthermore, despite a high prevalence of stunted and underweight children (53% and 25.8%, respectively), the low levels of anti-diphtheria antibodies were not correlated to the nutritional status. CONCLUSIONS: Our data highlight a significant deficit in both the vaccination coverage and diphtheria vaccine effectiveness within the Huaphan Province. Technical defi-ciencies in the methods of storage and distribution of vaccines as well as unreliability of vac-cination cards are discussed. Several hypotheses are advanced to explain such a decline in immunity against diphtheria and recommendations are provided to prevent future outbreaks.